Peran Orang Tua Terhadap Motivasi Belajar Anak Pada Masa Pandemi Covid-19 - Sitti ‘Abidah (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
This study aims to determine the role of parents in motivating children to learn during the COVID-19 pandemic. The research method used is qualitative research methods. This type of research leads to phenomenological studies which have special attention to the phenomena under study, focus on the activities of the research subject, reveal problems, present and analyze data, and obtain data by direct observation. The study was conducted within 1 month when the pandemic took place. The subjects of this study were parents who have children aged 5 to 9 years. The research begins by determining the problem to be studied, namely the role of parents in motivating children to learn. The data was collected by means of a questionnaire, then formulated the results of the research as a sign of the achievement of the research objectives. The results of the study found that the role of parents is needed in motivating children to learn during the Covid-19 pandemic. Parents as primary educators must provide a fun learning environment and time so that children can develop their abilities and achieve learning goals. Parents agree that during learning from home, the role of parents in motivating children to learn is the most important thing.